The Growing Threat of Gonococcal Blindness - Victoria Dolange; Colin P. Churchward; Myron Christodoulides; Lori A. S. Snyder (MDPI AG, 2018)
Antibiotic-resistant gonorrhea is now a reality, as well as the consequences of untreatable infections. Gonococcal eye infections result in blindness if not properly treated; they accounted for the vast majority of infections in children in homes for the blind in the pre-antibiotic era. Neisseria gonorrhoeae infects the eyes of infants born to mothers with gonorrhea and can also infect the eyes of adults. Changes in sexual practices may account for the rise in adult gonococcal eye infections, although some cases seem to have occurred with no associated genital infection. As gonorrhea becomes increasingly difficult to treat, the consequences for the treatment of gonococcal blindness must be considered as well. Monocaprin was shown to be effective in rapidly killing N. gonorrhoeae, and is non-irritating in ocular models. Repeated passage in sub-lethal monocaprin induces neither resistance in gonococci nor genomic mutations that are suggestive of resistance. Here, we show that 1 mM monocaprin kills 100% of N. gonorrhoeae in 2 min, and is equally effective against N. meningitidis, a rare cause of ophthalmia neonatorum that is potentially lethal. Monocaprin at 1 mM also completely kills Staphylococcus aureus after 60 min, and 25 mM kills 80% of Pseudomonas aeruginosa after 360 min. Previously, 1 mM monocaprin was shown to eliminate Chlamydia trachomatis in 5 min. Monocaprin is, therefore, a promising active ingredient in the treatment and prophylaxis of keratitis, especially considering the growing threat of gonococcal blindness due to antimicrobial resistance.